Analisis Determinan Transfer Pricing pada Perusahaan Multinasional yang Terdaftar di Bursa Efek Indonesia - Gracia Agata; Putu Indrajaya Lembut; Fitri Oktariani (Jurnal Ilmiah Wahana Akuntansi, 2021)
This study aims to analyze the effect of Multinationality, Tax Haven and Thin Capitalization on Transfer Pricing. The samples in this study were all multinational companies listed on the Indonesia Stock Exchange from 2016 to 2019 in addition to the financial, insurance, mining, and property sectors. The amount of data in accordance with the sample criteria is 260 data consisting of 65 companies for each year. The analytical method used in processing data using multiple linear analysis. This study uses the Statistical Package for Social Sciences (SPSS) program. The results showed that multinationality and tax havens had no effect on transfer pricing, and thin capitalization had a positive effect on transfer pricing.